nilai-nilai budaya Analisis Nilai-Nilai Budaya dalam lirik lagu Batak Toba Album Dorman Manik feat Rany Simbolon: Analisis Nilai-Nilai Budaya dalam lirik Lagu Batak Toba Album Dorman Manik feat Rany Simbolon - Limbong, Nathasya TriOlivia; Suhardi; Tety Kurmalasari; Isnaini Leo Shanty; Fabio Testy Ariance Loren; Zaitun (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The song belongs to the literary genre in which poets and writers have used words to convey their emotions. These heartfelt declarations and the lyrics' commentary on duties and love between humans represent culture in day-to-day living. Toba batak songs from the dorman bead feat rany symbolon album many contain cultural values. This study used a qualitative, descriptive methodology that made use of textual content. The data completed in this study consists of data obtained from the quotes from the fi fi album dorman manik feat rany symbolic. Based on the results of research, it can be summed up in ten songs in almeans dorman manik feat rany symbolon discovered cultural values (a) cultural values in human relations with god (b) cultural values in human relations with nature. (c) cultural values in human relationships with society (d) cultural values in human relationships with other humans (e) cultural values in man's relationship with himself